Ustilago maydis yeast stage found on imported sweet corn - Toome-Heller, Merje; Alexander, Brett J.R. (New Zealand Plant Protection, 2019)
During the inspection of imported sweet corn (Zea mays), a specimen with dry rot symptoms was detected by Ministry for Primary Industries quarantine officers. A sample was sent to the MPI Plant Health and Environment Laboratory for diagnostics, and initial examination found a layer of yeast cells on the surface of the symptomatic tissue. The fungus was cultured and identified based on DNA sequences as Ustilago maydis. While the corn-smut pathogen U. maydis is well known to cause tumour like galls on corn kernels, it is a less recognised fact that this fungus can also grow as a yeast. To determine if the yeast stage could have been associated with the dry-rot symptoms observed on the specimen, healthy material was inoculated with the isolated U. maydis strain. No symptoms developed on inoculated material, indicating that the yeast cells were likely multiplying on the surface of the cut corn ear as saprobes. To our knowledge, this is the first report of U. maydis yeast stage on corn ears and indicates a previously unconsidered pathway for the organism. For the yeast stage to cause disease, mating with a compatible mating type on the surface of a living host plant would be required.